THE EFFECT OF GIVING MUNG BEAN EXTRACT ON HEMOGLOBIN LEVELS OF MIDWIFERY STUDENTS OF LEVEL III OF MINISTRY OF HEALTH POLTECHNIC, TANJUNGPINANG - Susilawati, Elly; Febriani, Hanifah; Yanti, Yanti; Lailiyana, Lailiyana (JURNAL IBU DAN ANAK, 2025)
Adolescents with iron deficiency anemia are a group prone to anemia. Data from the Tanjungpinang City Health Office in 2018 showed that the incidence of anemia in adolescent girls was 25% of the total number of adolescent girls in Tanjungpinang City. The purpose of this study was to determine the effect of giving green bean juice on hemoglobin levels of female students at the Poltekkes Kemenkes Tanjungpinang. This study was conducted in January - May 2020 at the Poltekkes Kemenkes Tanjungpinang with this type of research being Quasy Experiment and post test only with control group design. Sampling in this study used the Purposive Sampling technique. The population in this study were all female students of DIII Midwifery Level III. The average hemoglobin level in the group given Fe tablets after being given Fe tablets was 13.67 gr / dl and the average hemoglobin level in the intervention group after being given green bean juice and Fe tablets was 12.32 gr / dl. The results of the Independent Test with a 95% confidence level showed no effect of green bean juice on hemoglobin levels in female students of the Tanjungpinang Ministry of Health Polytechnic (p = 0.209). It is expected that female students consume supplements containing iron, especially during menstruation and consume foods that contain a lot of substances that accelerate iron absorption